StudentSphere: Development of a Digital Gallery Platform for Publishing and Exploring Student Work - Muhammad Iqbal Fahrezzi; Khairany Zuhriyyah Jinan Hsb; Augis Dinanti; Debi Yandra Niska (Komunitas Dosen Indonesia, 2025)
StudentSphere is a digital gallery platform designed to enhance the visibility, accessibility, and academic value of student works in higher education. Recent studies show that universities in Indonesia lack centralized and user-friendly systems for showcasing academic outputs, leading to low discoverability and limited recognition of student achievements. This research aims to develop and evaluate StudentSphere as an institutional-level solution that provides structured publication workflows, efficient search mechanisms, and lecturer–student academic profiling. The platform was built using Laravel 10 and MySQL 8, supported by Tailwind CSS and Alpine.js for lightweight interaction, and evaluated through a multi-phase usability study. The research employed iterative Agile development, involving 57 participants (45 students and 12 lecturers) across five evaluation cycles including surveys, interviews, usability tests, and user acceptance testing. Results show strong usability with a System Usability Scale (SUS) score of 79.8, a task completion rate of 93%, and a satisfaction score of 4.25/5. Load testing also demonstrated stable performance for up to 200 concurrent users. Practical implications include improved academic visibility, streamlined work submission, and enhanced lecturer access to student achievements. However, limitations remain in institutional authentication and real-time engagement features. The study concludes that StudentSphere meets its intended goals, though future development should prioritize SSO integration, analytics, and real-time notifications to strengthen scalability and interoperability.